The Influence of Gamification and Perceived Value on Purchase and Continuance Use Intention towards Shopee in Indonesia - Budiman, Arief; Gouw, Michelle Arifin; Su, Kenny; Amelia, Novi (Kajian Branding Indonesia, 2024)
This study investigates gamification's impact on purchase intention, continuance use intention, and perceived value in Indonesian e-commerce, focusing on Shopee Cocoki. Using quantitative methods and SEM-CB analysis, 340 active Shopee users who played Shopee Cocoki were surveyed. Results show gamification positively affects purchase and continuance use intentions, though some findings differ from previous studies, such as social value not significantly impacting game use intention. Recommendations include emphasizing game use intention as an intermediary for consumer decisions and focusing on utilitarian, social, and hedonic values that influence purchase and continuance use intentions. These insights can formulate marketing strategies to enhance platform satisfaction by understanding consumer value priorities.